The impact of healthcare professionals' personality and religious beliefs on the decisions to forego life sustaining treatments: an observational, multicentre, cross-sectional study in Greek intensive care units. Issue 7 (21st July 2017) - Ntantana, Asimenia; Matamis, Dimitrios; Savvidou, Savvoula; Marmanidou, Kyriaki; Giannakou, Maria; Gouva, Μary; Nakos, George; Koulouras, Vasilios
Abstract : Objectives: To assess the opinion of intensive care unit (ICU) personnel and the impact of their personality and religious beliefs on decisions to forego life-sustaining treatments (DFLSTs). Setting: Cross-sectional, observational, national study in 18 multidisciplinary Greek ICUs, with >6 beds, between June and December 2015. Participants: 149 doctors and 320 nurses who voluntarily and anonymously answered the End-of-Life (EoL) attitudes, Personality (EPQ) and Religion (SpREUK) questionnaires. Multivariate analysis was used to detect the impact of personality and religious beliefs on the DFLSTs. Results: The participation rate was 65.7%. Significant differences in DFLSTs between doctors and nurses were identified. 71.4% of doctors and 59.8% of nurses stated that the family was not properly informed about DFLST and the main reason was the family's inability to understand medical details. 51% of doctors expressed fear of litigation and 47% of them declared that this concern influenced the information given to family and nursing staff. 7.5% of the nurses considered DFLSTs dangerous, criminal or illegal. Multivariate logistic regression identified that to be a nurse and to have a high neuroticism score were independent predictors for preferring the term 'passive euthanasia' over 'futile care' (OR 4.41, 95% CI 2.21 to 8.82, p<0.001,  and OR 1.59, 95% CI 1.03 to 2.72, p<0.05,  respectively). Furthermore, to be a nurse and to have a high-trust religious profile were related to unwillingness to withdraw mechanical ventilation. Fear of litigation and non-disclosure of the information to the family in case of DFLST were associated with a psychoticism personality trait (OR 2.45, 95% CI 1.25 to 4.80, p<0.05). Conclusion: We demonstrate that fear of litigation is a major barrier to properly informing a patient's relatives and nursing staff. Furthermore, aspects of personality and religious beliefs influence the attitudes of ICU personnel when making decisions to forego life-sustaining treatments.